Global Warming E-Books based on Learning style: Is it Effective to Enhance Students’ Problem-Solving Skills? - Luthfiana, Aisyah; Farhan, Muhammad; Jumadi, Jumadi; Nugroho, Muhammad; Rudin, Irfandi (JIPF (Jurnal Ilmu Pendidikan Fisika), 2025)
This study was conducted to assess the effectiveness of using physics e-books adapted to learning style in understanding material about global warming and improving students’ problem-solving skills. The independent variable in this study was the use of physics e-books based on learning style in global warming material, while the dependent variable was students’ skills to solve related problems. The research method used was pre-experimental with a one-group pretest-posttest design at SMAN 10 Yogyakarta, involving 61 grade X students who were selected using a purposive sampling technique. Assessment of students’ problem-solving skills is carried out by referring to previously established indicators. The data were then analyzed using SPSS, including tests for normality, homogeneity, one-way ANOVA, and N-gain. The research results indicated that although students' problem-solving abilities were in the moderate category, the use of physics e-books integrating students' learning styles significantly improved their understanding of global warming material. This indicates that the use of electronic teaching materials that are adapted to students' learning styles can have a positive impact on their cognitive development. Thus, students can learn more effectively by adhering to their respective learning styles and overcoming learning challenges through the guidance provided in the e-book.